Seeing Things Within and Beyond the Mirror: An Analysis of Virginia Woolf’s “The Lady in The Looking Glass: A Reflection” - Kainat Zeb (University of Chitral Journal of Linguistics and Literature)
Virginia Woolf a highly appreciated writer both for her literary-critical insight and innovative writing techniques explores the role and character of women in society to reveal the truth and reality of their nature. Woolf in her works surfaces forth the inner discomfort of apparently integrated and a whole individual. In “The Lady in The Looking Glass: A Reflection” (1929), Woolf employs the stream of consciousness technique to communicate the thoughts of a narrator who ponders an image of Isabella Tyson to unveil the nature of truth and reality of her person by opening the intricate layers of her appearance. This paper explores the concept of the split self with reference to the character of Isabella to see the impact of the other on/in the construction of self. Lacan’s concept of mirror stage is used as a theoretical framework to see how Isabella’s character is put in the external symbolic order and is alienated from its own history to examine how the self can be conceptualized and effected by the interplay of various forces and the inside form in and through other. This study demonstrates that Isabella’s self-image is the distorted product of the ideal ego and ego ideal and is made and changed by acting towards others to make them believe what they see in her as true of her.